Orientation of colonized sand flies Phlebotomus papatasi, P. duboscqi, and Lutzomyia longipalpis (Diptera: Psychodidae) to diverse honeys using a 3‐chamber in‐line olfactometer. Issue 1 (June 2014) - Wasserberg, G.; Kirsch, P.; D. Rowton, E.
ABSTRACT A 3‐chamber in‐line olfactometer designed for use with sand flies is described and tested as a high‐throughput method to screen honeys for attractiveness to Phlebotomus papatasi (four geographic isolates), P. duboscqi (two geographic isolates), and Lutzomyia longipalpis maintained in colonies at the Walter Reed Army Institute of Research. A diversity of unifloral honey odors were evaluated as a proxy for the natural floral odors that sand flies may use in orientation to floral sugar sources in the field. In the 3‐chamber in‐line olfactometer, the choice modules come directly off both sides of the release area instead of angling away as in the Y‐tube olfactometer. Of the 25 honeys tested, five had a significant attraction for one or more of the sand fly isolates tested. This olfactometer and high‐throughput method has utility for evaluating a diversity of natural materials with unknown complex odor blends that can then be down‐selected for further evaluation in wind tunnels and/or field scenarios.